Relationship between basic anthropometric measurements an ranking in elite women alpine skiing - Hraski, M.; Hraski, Z.; Mikulic, P. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Skiing is a highly demanding Sport that requires a high level of skier's physical efficiency. However, as is the case in other sports, two of the limiting factors in achieving the top-level results are also body mass and stature. Therefore, the aim of this investigation is to determine the basic anthropometric models of elite female alpine skiers in relation to their classification on the most important international competitions.